2010
DOI: 10.5625/lar.2010.26.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Luteolin Liposome Solution by Animal Model for Atopic Dermatitis in NC/Nga Mice

Abstract: Atopic dermatitis is a common chronic inflammatory skin disease, associated with marked inflammatory cells (of mast cells and eosinophils) and severe itching, which leads to clinical problems in the pediatric population. This study was designed to investigate the inhibitory effects of luteolin liposome solution, that is entrapped the hydrophobic luteolin (one of the flavonoids) into ethosome to improve its stability, by using hapten-induced atopic dermatitis animal model (NC/Nga mice).The luteolin liposome tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…It has been well established that flavonoid-rich plants can be good sources of antioxidants with therapeutic potential [33]. Some flavonoids, such as astragalin and luteolin, have been reported to ameliorate atopic skin symptoms in murine models of AD [34,35], which suggests the suppression of oxazolone and DNCB-induced AD by SCAE possibly reflects the presence of flavonoids. In this study, HPLC analysis of SCAE confirmed luteolin, luteolin 7-O-glucoside, and umbelliferone as main compounds of S. chamaejasme.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well established that flavonoid-rich plants can be good sources of antioxidants with therapeutic potential [33]. Some flavonoids, such as astragalin and luteolin, have been reported to ameliorate atopic skin symptoms in murine models of AD [34,35], which suggests the suppression of oxazolone and DNCB-induced AD by SCAE possibly reflects the presence of flavonoids. In this study, HPLC analysis of SCAE confirmed luteolin, luteolin 7-O-glucoside, and umbelliferone as main compounds of S. chamaejasme.…”
Section: Discussionmentioning
confidence: 99%